Hollow cathode magnetron deposition of AlN thin films: crystalline structure and morphology - Pessoa,R. S. (2006)
A new dc hollow cathode plasma source has been assembled whith a conventional planar magnetron cathode used together with another plane cathode plate to form a hollow cathode cavity. The system comprises two cathode plates of aluminium separated by a distance d, one of them acting as target of the magnetron cathode, the other being an ordinary plate. The discharge anode is a metallic flange of the vacuum chamber. This leads to enhanced ionization in the cathode cavity region and enables the discharge to operate at significantly lower pressures than for a typical planar magnetron configuration. As a consequence, sputtered atoms can reach a substrate with minimum energy loss due to collisions with filling gas atoms. The discharge gas was a mixture of argon and nitrogen. AlN thin films were grown on silicon substrates, at ambient temperature, and characterized with respect to the structure and morphology by XRD and AFM analyses respectively. The structure and roughness of the AlN films were studied as a function of the deposition parameters.